2016
DOI: 10.1007/s10753-016-0374-7
|View full text |Cite|
|
Sign up to set email alerts
|

Geraniin Inhibits LPS-Induced THP-1 Macrophages Switching to M1 Phenotype via SOCS1/NF-κB Pathway

Abstract: M1 macrophage polarization is proved to promote inflammation in atherosclerosis process. In this study, we evaluated the inhibitory effect of geraniin, a bioactive polyphenolic compound, on the LPS-induced switch of THP-1 macrophages to M1 phenotype, and we propose a molecular basis for its action. Flow cytometry analysis indicated that geraniin significantly inhibited LPS-induced M1 macrophage polarization. Geraniin downregulated the protein and the mRNA level of typical cytokines of M1 macrophage, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Geraniin was found to inhibit LPS-induced inflammation in RAW264.7 cells [12]. Also, geraniin was found to inhibit LPS-induced THP-1 macrophages switching to M1 phenotype [13]. Furthermore, it has been reported that geraniin protected cells from H 2 O 2 -induced oxidative cell death [14].…”
Section: Introductionmentioning
confidence: 99%
“…Geraniin was found to inhibit LPS-induced inflammation in RAW264.7 cells [12]. Also, geraniin was found to inhibit LPS-induced THP-1 macrophages switching to M1 phenotype [13]. Furthermore, it has been reported that geraniin protected cells from H 2 O 2 -induced oxidative cell death [14].…”
Section: Introductionmentioning
confidence: 99%
“…Suppressor of cytokine signaling 1 (SOCS1) is a protein, expressed in lymphocytes and microglial cells [17, 18]. Overexpression of SOCS1 protein decreases the activation of macrophage in the peripheral tissue and microglia in the CNS [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that we chose the antibodies used to demonstrate M1 versus M2 macrophages based on prior studies, but there is controversy as to the most appropriate method for characterizing different macrophage phenotypes. Among multiple models and studies, similar to our model of aneurysm repair, in murine models of remodeling of murine myocardial infarction, CD206+ ‘M2’ macrophages mediate repair, therefore, we used CD206 as a marker for M2 reparative macrophages,14 15 and iNOS has been commonly used as a marker for M1 macrophage phenotype 16. However, no precise method for identifying M1 versus M2 macrophages has been agreed.…”
Section: Discussionmentioning
confidence: 99%